The Prohibition of Sampir Marriage in the Perspective of Maslahah Mursalah - Nurwakhid Agung Kurniawan (Journal of Law and Legal Reform, 2020)
Sampir marriages are marriages between men and women separated from the road, these marriages are prohibited according to the adat community of Kenteng Village, Toroh District, Grobogan Regency. This study aims to, 1) describe the prohibition of "sampir" marriage from the perspective of "maslahah mursalah", 2) develop knowledge in terms of Indonesian marriage law, 3) provide understanding to the village community in the village regarding the "prohibition of marriage of the sampir" perspective "maslahah mursalah". This research is an empirical study, or it can also be called field research that examines the tradition of prohibiting marriage in Kenteng Village, Toroh Sub-District, Grobogan Regency. This research includes empirical research. Data collection by observation, interview, and documentation. The author uses a qualitative method of deductive thinking in analyzing this problem, namely the process of approach that departs from general truth about a phenomenon or theory and generates that truth on an event that is characterized by the same phenomenon concerned. Overview of Islamic Law on the tradition of prohibiting marriages of sampir in Kenteng Village, Toroh Sub-District, Grobogan Regency, through the Maá¹£laá¸¥ah approach, it is a mistake that the tradition contains an element of shirk because the community believes that sampir marriage will bring disaster to the perpetrators, the community always associates the disaster that befell the marriages of the sampir perpetrators. mate sampir.